Key parameters linking cyber-physical trust anchors with embedded internet of things systems - Maasberg, Michele; Butler, Leslie G.; Taylor, Ian (Frontiers in Communications and Networks, 2023)
Why will a modern automobile, with over 100 million lines of code, tolerate the installation of counterfeit parts? We start with this provocative question as a driver for the discussion of counterfeit parts in the supply chain, the impact on driver safety, and the recommendations in a recent report on secure supply chains. Integration of the Internet of Things (IoT) in the automotive industry has brought benefits as well as security challenges, particularly counterfeiting. Demand for counterfeit automotive parts has nearly tripled in the wake of the global COVID-19 pandemic due to increased costs and shortage of replacement parts. Counterfeiters tend to focus on parts most often replaced. Consequently, brake and ignition systems components rank among the most frequently counterfeited repair parts. Leading anti-counterfeiting strategies for automotive parts are visual inspection of the packaging and purchase from valid suppliers. However, these strategies are ineffective with the increasing sophistication of counterfeiters. For example, in Australia, approximately 62% of Toyota brand automobile parts sold online were fake, even with improvements to packaging. Recent U.S. law enforcement agency investigations also revealed deceptive packaging on counterfeit parts, including brake and ignition system components. In this study, we review current anti-counterfeiting techniques and develop a new anti-counterfeiting authentication process. The process is based on a trust anchor hardware authentication mechanism and key parameters linking it to database, traceability and monitoring systems. The work includes a new linking parameter based on the acoustic signature of tires as part of a blockchain-based cyber-physical trust anchor.